Genome-Wide Identification of Genes Important for Growth of Dickeya dadantii and Dickeya dianthicola in Potato (Solanum tuberosum) Tubers - Helmann, Tyler C.; Filiatrault, Melanie J.; Stodghill, Paul V. (Frontiers in Microbiology, 2022)
Dickeya species are causal agents of soft rot diseases in many economically important crops, including soft rot disease of potato (Solanum tuberosum). Using random barcode transposon-site sequencing (RB-TnSeq), we generated genome-wide mutant fitness profiles of Dickeya dadantii 3937, Dickeya dianthicola ME23, and Dickeya dianthicola 67-19 isolates collected after passage through several in vitro and in vivo conditions. Though all three strains are pathogenic on potato, D. dadantii 3937 is a well-characterized model while D. dianthicola strains ME23 and 67-19 are recent isolates. Strain ME23 specifically was identified as a representative strain from a 2014 outbreak on potato. This study generated comparable gene fitness measurements across ecologically relevant conditions for both model and non-model strains. Tubers from the potato cultivars “Atlantic”, “Dark Red Norland”, and “Upstate Abundance” provided highly similar conditions for bacterial growth. Using the homolog detection software PyParanoid, we matched fitness values for orthologous genes in the three bacterial strains. Direct comparison of fitness among the strains highlighted shared and variable traits important for growth. Bacterial growth in minimal medium required many metabolic traits that were also essential for competitive growth in planta, such as amino acid, carbohydrate, and nucleotide biosynthesis. Growth in tubers specifically required the pectin degradation gene kduD. Disruption in three putative DNA-binding proteins had strain-specific effects on competitive fitness in tubers. Though the Soft Rot Pectobacteriaceae can cause disease with little host specificity, it remains to be seen the extent to which strain-level variation impacts virulence.